2023
DOI: 10.3390/app13127272
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Critical Nodes in Temporal Networks by Dynamic Graph Convolutional Networks

Abstract: Many real-world systems can be expressed in temporal networks with nodes playing different roles in structure and function, and edges representing the relationships between nodes. Identifying critical nodes can help us control the spread of public opinions or epidemics, predict leading figures in academia, conduct advertisements for various commodities and so on. However, it is rather difficult to identify critical nodes, because the network structure changes over time in temporal networks. In this paper, cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…In Refs. [24–29], there is little focus on evaluating OT assets, which can be considered an important issue that needs to be covered to ensure that the field of CPSs is equivalently secured from both OT and IT aspects. Additionally, while conducting this research, it has been found that there are no relevant existing review papers exploring studies for evaluating asset criticality in different CPSs.…”
Section: Introductionmentioning
confidence: 99%
“…In Refs. [24–29], there is little focus on evaluating OT assets, which can be considered an important issue that needs to be covered to ensure that the field of CPSs is equivalently secured from both OT and IT aspects. Additionally, while conducting this research, it has been found that there are no relevant existing review papers exploring studies for evaluating asset criticality in different CPSs.…”
Section: Introductionmentioning
confidence: 99%